Q: What is -5a plus 2b plus 3a plus b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

Gathering like terms together, this is equal to 5a + 3b + 7c.

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

3a + 2b is an expression in algebra. If you make 3a + 2b equal to something then you can find the values of "a" and "b" Lets say you make 3a + 2b equal to 23 3a + 2b = 23 Now find "a" and "b" to make this equation true... 3(5) + 2(4) = 23 15 + 8 = 23 23 = 23 Correct So in this case a=5 and b=4

Related questions

The given expression can be simplified to: 3b-a

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

1

Gathering like terms together, this is equal to 5a + 3b + 7c.

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

7a-2b

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

= a + b - 2

5a(a+2b+b²)

What is the answers to -7 ( a + b - 5 ) + 8 ( -3a +2b ) + b ( 7 + 3 )

From your description, I get: a + b + c = 180b - 3a c = 5a You have two equations and three unknowns, which is unsolvable.